ПРОСПЕКТИВНЫЕ ИССЛЕДОВАНИЯ И АНАЛИЗ ЗАБОЛЕВАЕМОСТИ КРУПНОГО И МЕЛКОГО РОГАТОГО СКОТА В ФЕРМЕРСКИХ ХОЗЯЙСТВАХ НЕКОТОРЫХ РЕГИОНОВ КАЗАХСТАНА - А. Абуталип; М. Касенов; В. Сущих; А. Мусаева; Н. Егорова; Б. Айтжанов; Е. Оспанов; К. Майхин; G. Kydyrova; М. Кадыркулова (Animal Health and Biosafety, 2026)
Animal husbandry is a fundamental element of the agro-industrial complex of the Republic of Kazakhstan, occupying one of the leading positions in terms of production and economic importance. However, the dynamic development of the industry is accompanied by serious challenges, the main one of which remains the problem of livestock health. There is a need for a systematic analysis of the morbidity structure of farm animals, which serves as a basis for the development of preventive and curative measures aimed at reducing economic losses and increasing livestock productivity. The purpose of the study is to conduct a prospective analysis of the incidence of cattle and small cattle in farms in various regions of Kazakhstan. Diseases of various etiologies were considered: non-infectious pathologies, obstetric and gynecological disorders and infectious diseases. The methodology included an analysis of official veterinary reports, clinical observations and laboratory data for 2024-2026, which allowed taking into account seasonal fluctuations, climatic factors and the peculiarities of the transition period in the development of animal husbandry. The results showed that the main share is made up of non-communicable diseases caused by violations of feeding and maintenance standards. The second place is occupied by obstetric and gynecological pathologies (endometritis, metritis, afterbirth retention, infertility) that affect the reproductive potential of the herd. Infectious diseases manifest themselves in local outbreaks, but retain epizootological significance and require strict control. Research indicates the need to strengthen veterinary and sanitary supervision, the introduction of early monitoring systems and digital technologies. Improving the quality of feeding, preventing reproductive disorders, and using modern diagnostic methods, including rapid tests and molecular genetic research, remain key areas. This will make it possible to identify infectious agents faster, reduce the burden of antibiotics and increase the overall efficiency of animal husbandry.